Seasonal variations of siliceous microplankton fluxes and radiolarian assemblages linked to environmental conditions in Prydz Bay polynya, Eastern Antarctica - Zhang, Haifeng; Wang, Rujian; Han, Zhengbing; Sun, Yongming; Fan, Gaojing; Zhao, Jun; Hu, Ji; Ren, Jian; Pan, Jianming (Frontiers in Marine Science, 2023)
Siliceous microplankton is an effective proxy for connecting modern and past marine environments; however, radiolarians have been understudied in Prydz Bay, Eastern Antarctica. This study investigated the changes in the siliceous microbiota fluxes and radiolarian assemblages captured in a 1-year time-series sediment trap (February 2014 to February 2015, ~490 m water depth) in the polynya of Prydz Bay. The results exhibited the strong seasonality in the radiolarian assemblages and the fluxes of radiolarians, diatoms, silicoflagellates and sponge spicules, with low numbers in winter and high numbers in summer. Seasonal variations in the sea ice and plankton community were critical in these patterns. The total radiolarian flux (TRF) displayed three peaks with higher flux than the annual average TRF over the year, all of which occurred in summer. These TRF peaks were mainly driven by seasonal fluctuations of sea ice, primary productivity, grazing pressure caused by phytophagous zooplankton and resuspension of small radiolarians in the surface sediments induced by modified Circumpolar Deep Water (mCDW) intrusion onto the shelf. There were also two notable low-TRF stages, mainly related to full sea-ice coverage and high grazing pressure. Two dominant assemblages were recognized by means of Q-factor analysis. Dominant assemblage one was composed of three small-sized taxa, Antarctissa sp., Phormacantha hystrix and Plectacantha oikiskos, which could be used as a proxy for primary productivity in the Marginal Ice Zone (MIZ) in Prydz Bay. Dominant assemblage two was composed of Antarctissa strelkovi and Antarctissa denticulata, with A. strelkovi dominating. The high flux and high relative abundance of A. strelkovi marked the extension of Ice Shelf Water (ISW) to the shelf area in Prydz Bay. These findings will provide new insights and reliable proxies for modern and paleoceanographic research in the Southern Ocean.